2019
DOI: 10.1136/bmjopen-2018-026895
|View full text |Cite
|
Sign up to set email alerts
|

Aetiology and risks factors associated with the fatal outcomes of childhood pneumonia among hospitalised children in the Philippines from 2008 to 2016: a case series study

Abstract: ObjectivePneumonia remains the leading cause of hospitalisations and deaths among children aged <5 years. Diverse respiratory pathogens cause acute respiratory infections, including pneumonia. Here, we analysed viral and bacterial pathogens and risk factors associated with death of hospitalised children.DesignA 9-year case series study.SettingTwo secondary-care hospitals, one tertiary-care hospital and one research centre in the Philippines.Participants5054 children aged <5 years hospitalised with severe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 75 publications
4
25
1
2
Order By: Relevance
“…In some studies, RSV detection was more than 3 times greater than the next leading pathogen [ 14 ]. Reported RSV positivity rates in tropical Asian countries range from 9% to 50% depending on the geographic location and sample population ( Table 1 ) [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. Not unexpectedly, an increased risk for RSV infection has been noted in infants with chronic lung disease, neurodevelopmental conditions and congenital heart disease, with repeated infections associated with asthma and atopy among the children and their families [ 15 ].…”
Section: Rsv Disease Activity Across Tropical Asiamentioning
confidence: 99%
“…In some studies, RSV detection was more than 3 times greater than the next leading pathogen [ 14 ]. Reported RSV positivity rates in tropical Asian countries range from 9% to 50% depending on the geographic location and sample population ( Table 1 ) [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. Not unexpectedly, an increased risk for RSV infection has been noted in infants with chronic lung disease, neurodevelopmental conditions and congenital heart disease, with repeated infections associated with asthma and atopy among the children and their families [ 15 ].…”
Section: Rsv Disease Activity Across Tropical Asiamentioning
confidence: 99%
“…Tsou showed patients with underlying condition, especially neurologic diseases were more likely suffering ADV infections (23). One study about risk factors associated with mortality of pneumonia children reported malnutrition was the most common factor related with fatality (24). The study of Zampoli et al in South Arica reported that ADV associated pneumonia children reported 34.0% were malnourished (25).…”
Section: Discussionmentioning
confidence: 99%
“…Esta cifra es más elevada de la observada en otras series, como en (12) el estudio de Fritz CQ et al donde la frecuencia de choque en niños que requirieron hospitalización fue del 30%. De los datos laboratoriales, la frecuencia de trombocitopenia<150000/mm³ y la anemia severa (Hb ≤ 8 gr/dl) fueron más frecuentes en aquellos pacientes que se hospitalizaron en UCI, lo cual ya fue (21) observada en otros estudios .…”
Section: Discussionunclassified
“…Los pacientes que fallecieron fueron los de menor edad (≤3 meses), tuvieron neumonía grave (complicada con derrame pleural o neumotorax), ingresaron en choque o con insuficiencia respiratoria. Este cuadro clínico es característico de pacientes que (12,21) se hospitalizaron en UCI en otras series .…”
Section: Discussionunclassified